Optimal pricing and production lot-sizing for seasonal products over a finite horizon. (16th August 2010) - Saha, Subrata; Das, Sambhu; Basu, Manjusri
In day-to-day time-based competition, the unit selling price of a hightech product declines significantly over its short life cycle. In this paper, we introduce dynamic pricing to traditional Economic production quantity (EPQ) models for time and price sensitive products. From manufacturer/producer point of view, the model is developed to maximise total profit. We prove that the total profit is a concave function of selling price within fixed planning horizon. A solution procedure is presented to determine optimal prices, optimal number of production cycles, optimal lot size and optimal profit simultaneously. We illustrate the model with numerical examples and sensitivity analysis is also performed.